Absolute sustainability of New Zealand office buildings in the context of climate targets. (November 2021) - Bullen, L.; McLaren, S.J.; Dowdell, D.; Chandrakumar, C.
Abstract: An LCA-based absolute environmental sustainability approach was used to assess the performance of New Zealand office buildings in the context of climate targets for the period 2018–2050. It was found that the carbon footprint of the New Zealand office building sector for 2018–2050 (8566 ktCO2eq ) exceeded the carbon budget (2140 ktCO2eq ) by a factor of 4.0. The new build stock contributed approximately 55 % of the total office building sector carbon footprint. Operational energy use accounted for 86 % and 36 % of the existing and new build stock carbon footprints, respectively. Raw material supply, construction and manufacture contribute 53 % of the new build stock carbon footprint. For an individual new build office over a 60-year service life, the carbon footprint (1259 tCO2eq ) exceeded the carbon budget (236 tCO2eq ) by a factor of 5.3. A sensitivity analysis of the results to various input parameters was undertaken. It was found that methodological choices can significantly increase or decrease the available carbon budget and the carbon footprint. The use of alternative global climate targets or grandfathering years, inclusion of mechanical, electrical and plumbing (MEP) and tenant improvement (TI) elements, and providing an alternative post-2050 use stage carbon budget for a new build office resulted in a >25 % change compared to the base case. The study highlighted the need for more accurate assessment of MEP and TI elements in New Zealand office buildings, and up-to-date and accurate multi-regional input-output consumption-based GHG emission data for New Zealand. Highlights: Carbon footprint of New Zealand office sector exceeds carbon budget by factor of 4. Carbon footprint of a new build office exceeds carbon budget by factor of 5. Methodological choices can increase or decrease the carbon budget and footprint. Highlights opportunities to reduce the carbon footprint of new build offices.